Analysis of the Influence of Twitter Social Media Rebranding on Customer Loyalty Through Customer Satisfaction as a Mediating Variable - Rio Tirtana (Lavish Opulent Education, 2024)
Twitter's social media has currently undergone a branding change and has an impact on its users. This study aims to find out and analyze the influence of Twitter social media branding changes on customer loyalty through customer satisfaction. The research methodology used is quantitative research with a survey approach using nonprobability sampling techniques. Data taken using the purpose sampling method was 205 samples. The data analysis technique used is a path analysis technique using the SPSS (Statistical Package for Social Sciences) analysis tool version 25. The results of the study show that rebranding has a significant positive effect on customer satisfaction. Rebranding and customer satisfaction have a significant positive effect on customer loyalty. Customer satisfaction moderates the relationship between rebranding and has a significant positive effect on customer loyalty